Micro-scale fracture experiments on zirconium hydrides and phase boundaries - Chan, H; Roberts, S; Gong, J (Elsevier, 2016)
Fracture properties of micro-scale zirconium hydrides and phase boundaries were studied using microcantilever testing methods. FIB-machined microcantilevers were milled on cross-sectional surfaces of hydrided samples, with the most highly-stressed regions within the δ-hydride film, within the α-Zr or along the Zr-hydride interface. Cantilevers were notched using the FIB and then tested in bending using a nanoindenter. Load-displacement results show that three types of cantilevers have distinct deformation properties. Zr cantilevers deformed plastically. Hydride cantilevers fractured after a small amount of plastic flow; the fracture toughness of the δ-hydride was found to be 3.3 ± 0.4 MPam1/2 and SEM examination showed transgranular cleavage on the fracture surfaces. Cantilevers notched at the Zr-hydride interface developed interfacial voids during loading, at loads considerably lower than that which initiate brittle fracture of hydrides.